2011
DOI: 10.1029/2010ja015632
|View full text |Cite
|
Sign up to set email alerts
|

Daytime longitudinal structures of electron density and temperature in the topside ionosphere observed by the Hinotori and DEMETER satellites

Abstract: [1] Daytime longitudinal structures of the electron density (N e ) and temperature (T e ) in the topside ionosphere observed by Hinotori and DEMETER are examined under various conditions of solar flux, local time, and seasons. Results from both satellites show a similar longitudinal N e structure in the morning from July to October, although the value of N e observed by Hinotori is higher than that of DEMETER owing to higher solar flux. This result implies that the longitudinal structure of N e may appear in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 48 publications
5
45
0
Order By: Relevance
“…7, a large-scale longitudinal structure, which is similarly reported by many scientists (e.g. Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…7, a large-scale longitudinal structure, which is similarly reported by many scientists (e.g. Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December.…”
Section: Resultssupporting
confidence: 83%
“…Sagawa et al, 2005;Immel et al, 2006;Lin et al, 2007;Kakinami et al, 2011), is clearly seen around the magnetic equator in the F3/C model. According to Kakinami et al (2011), the 4-peak structure of N e at 660 km observed with the DEMETER satellite is the most pronounced in September while a 3-peak structure appears in March and December. Though the IRI model also shows a longitudinal structure, the longitudinal structure retrieved with the F3/C model is more pronounced than that of the IRI and its seasonal variation agrees with previous studies.…”
Section: Resultsmentioning
confidence: 87%
“…The plasma parameters detected by the ISL have been used in many papers (Onishi et al 2009;Jhuang et al 2010;Kakinami et al 2011;Li et al 2011;Zhao et al 2013). Kakinami et al (2011) studied the daytime longitudinal structures of electron density and temperature in the topside ionosphere observed by the Hinotori and DEMETER satellites, which showed a similar longitudinal N e structure in the morning from July to October, and similar pronounced N e maxima in Southeast Asia, the Pacific Ocean and west of South America in the different solar flux conditions.…”
Section: Demeter Satellitementioning
confidence: 99%
“…The plasma parameters detected by the ISL have been used in many papers (Onishi et al 2009;Jhuang et al 2010;Kakinami et al 2011;Li et al 2011;Zhao et al 2013). Kakinami et al (2011) studied the daytime longitudinal structures of electron density and temperature in the topside ionosphere observed by the Hinotori and DEMETER satellites, which showed a similar longitudinal N e structure in the morning from July to October, and similar pronounced N e maxima in Southeast Asia, the Pacific Ocean and west of South America in the different solar flux conditions. In addition, Jhuang et al (2010) found a middle latitude enhancement in DEME-TER ISL data in the nighttime from September to April during 2005 -2009, consistent with the ionospheric F2 region observation detected with ionosonde, incoherent scatter radar and the techniques for GPS total electron content (TEC) (Jhuang et al 2010).…”
Section: Demeter Satellitementioning
confidence: 99%
See 1 more Smart Citation